A COMPARISON OF DIFFERENT RUBBER DAM SYSTEMS ON A DENTAL SIMULATOR - Martin Kapitán (Acta Medica, 2014)
The purpose of this study was to test the hypothesis that more recently developed rubber dam systems (OptraDam® Plus and OptiDam™) are faster and easier to handle, and that the quality of isolation is not decreased. The rubber dam systems were applied in standard conditions on a dental simulator in several model clinical situations. The time of preparation, application and removal were measured and the quality of isolation was evaluated. The median time of rubber dam placement was 51 s (Q1 = 38 s; Q3 = 79 s). The shortest median time of application was with OptiDam™ (42 s), followed by a conventional rubber dam (53 s), and finally the longest was with OptraDam® Plus (58 s). The median volume of fluid remaining in the isolated space after 5 minutes was 9.5 mL (Q1 = 8 mL; Q3 = 10 mL). The largest median volume of remaining water was with OptiDam™ (10 mL), followed by a conventional rubber dam (9.5 mL) and the least with OptraDam® Plus (8.5 mL). The afore-stated hypothesis about the advantages of modern rubber dam isolation systems was accepted for OptiDam™, but rejected for OptraDam® Plus. The results could contribute to decision-making concerning the choice of rubber dam system.